Potensi Maggot Black Soldier Fly Sebagai Pengurai Sampah Organik dengan Variasi Pakan - Diah Dianingtyas Sukardi; Bagus Dwi Setyawan (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Given the significant amount of organic waste generated daily by households in Yogyakarta, a number of initiatives and strategies are being employed to achieve effective waste management. One potential solution is the use of Black Soldier Fly (BSF) larvae as an alternative to high protein fish feed. The larval residue (frass), which contains a variety of nutrients, may also prove beneficial to plants. This research was conducted from January to March 2024 at the Solid Waste and Hazardous Waste Laboratory, Islamic University of Indonesia, Yogyakarta. The aim of this study is to determine the potential of BSF larvae and BSF frass as organic waste decomposers, using three different types of feed: mixed food waste, vegetable waste and leaf waste. A comparative analysis was carried out between the data obtained by the researchers and the quality standards established in the 2022 version of SNI 9043-4 for fish feed, and Ministerial Decree No. 261 of 2019 for solid organic fertilisers. The results show that BSF larvae fed with mixed food waste meet the quality standards for protein and fat content, with values above 35% and 5% respectively. In addition, the total NPK value of the BSF frass produced is above 2% and the C/N ratio is below 25%. Frass that meets these standards is produced from larvae fed on mixed food waste.